Pemberdayaan UMKM Masyarakat Melalui Digital Marketing Di Desa Jajar, Kecamatan Wates, Kabupaten Kediri - Mirfaqo, Nidaul Hasanah; Komariyah; Setiawati, Agustin (Institute for Research and Community Services, 2024)
The existence of Micro, Small and Medium Enterprises (MSMEs) is one of the community's economic activities that is currently being developed a lot. Because MSMEs are very useful to help fulfill the community's economy. This is influenced by the development of the times, then causes technology to grow rapidly. So that technological sophistication can be utilized in various aspects including being able to increase micro, small and medium enterprises (MSMEs). In order for the community's economy to remain stable, it is necessary to empower community MSMEs, one of which is by holding MSME outreach through digital marketing. By holding socialization activities for MSMEs using digital marketing in Jajar Village, it is a form of utilizing digital technology. The purpose of the MSME outreach activities in the village is to provide knowledge and insight about marketing MSME products in increasing their business with internet media in accordance with developments in this digital era. The method used in community empowerment is the Participatory, Action, Research (PAR) method which includes observation, interviews, documentation, training, mentoring, socialization and work practices. The output of socializing MSMEs with digital marketing in Jajar Village is that the community can increase their business productivity by improving more effective marketing methods using social media in accordance with increasingly sophisticated technological developments. And can market their business in a wider market. Keywords: Empowerment; UMKM; Digital Marketing